Surah-Surah Al-Qur’an untuk Bacaan Salat dalam Perspektif Hadis - Miftahudin Miftahudin; Salim Rosyadi; Mus’idul Millah (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2024)
Al-Qur’an, the holy book of Muslims, contains instructions and guidelines for the life of a Muslim. One of the important aspects of Islamic worship is prayer, which is obligatory for every Muslim. During the prayer, a number of surahs of the Quran are read in succession. There are several letters that the Prophet Muhammad SAW read in prayer, one of the letters that must be read in every prayer is the letter Al Fatihah. In addition to Al Fatihah, there are several other letters that the Prophet also recommended to read in prayer, not only about what letters the Prophet read in prayer, but the Prophet also ordered that the prayer readings be adjusted when serving as the priest for congregational prayers. The research shows the themes of hadith concerning what are the letters that the Prophet Muhammad SAW read in prayer and how the ethics are in reading the Koran when he becomes an imam in congregational prayers.